The Students’ Perceptions in Using TikTok as Media for Learning English Vocabulary on Autonomous Learning - Alamsyah Alamsyah; Fazri Nur Yusuf; Rojab Siti Rodliyah (Research Synergy Foundation, 2025)
Autonomous learning fosters students’ independence in managing their learning without teacher intervention. However, many students currently lack motivation for independent English vocabulary learning because of unengaging methods. The objective of this study is to determine students’ perceptions regarding the use of TikTok as a medium for learning English vocabulary for autonomous learning and improving their English vocabulary. This study employed qualitative research to analyze data, focusing on 5 AP2 students from a vocational high school in Bandung, Indonesia. The students were chosen as participants because they used TikTok as a medium for English vocabulary learning in autonomous learning. Additionally, the AP2 students were selected because their study program, Hospitality accommodation, involves frequent interaction with English vocabulary, making them more likely to engage with vocabulary learning platforms like TikTok. Data were gathered through interviews and analyzed using Miles and Haberman’s theory, which has three steps: reduce the data, display the data, and make a conclusion. The findings revealed that most students responded positively to using TikTok as a medium for autonomous English vocabulary learning, indicating that TikTok was effective in enhancing their vocabulary acquisition. The study concluded that TikTok is an effective and engaging medium for supporting autonomous English vocabulary learning, although potential distractions from the platform’s content should be considered.